2010
DOI: 10.1007/s00417-010-1546-z
|View full text |Cite
|
Sign up to set email alerts
|

Intraobserver and interobserver repeatability of ocular components measurement in cataract eyes using a new optical low coherence reflectometer

Abstract: The Lenstar LS 900® evidenced excellent repeatability and observers´ independent results of all components analyzed except white-to-white distance and corneal steepest meridian position measurements. To the best of our knowledge, this is the first study on interobserver repeatability of optical low-coherence reflectometry in cataract eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 21 publications
3
30
0
2
Order By: Relevance
“…The results of the present study demonstrated that all devices have high repeatability in healthy subjects and were in accordance with the literature (3,6,(9)(10)(11)(12)(13)(14)(15) . In addition, the FD-OCT exhibited slightly better repeatability compared with the other devices.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The results of the present study demonstrated that all devices have high repeatability in healthy subjects and were in accordance with the literature (3,6,(9)(10)(11)(12)(13)(14)(15) . In addition, the FD-OCT exhibited slightly better repeatability compared with the other devices.…”
Section: Discussionsupporting
confidence: 80%
“…It can measure 35,632 points on the anterior corneal surface and 30,000 on the posterior corneal surface, in high-resolution mode, in approximately 5-6 s. A pachymetric map is then reconstructed using the point-by-point anterior and posterior corneal surface data (10) . These non-contact instruments have been shown to have good repeatability in normal eyes (3,6,(9)(10)(11)(12)(13)(14)(15) . However, there are limited data available regarding the agreement among CCT measurements obtained using OLCR, FD-OCT, and SC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical low-coherence reflectometry (OLCR) biometer LENSTAR LS 900® is the newest generation of optical biometer [3][4][5][6][7][8][9]. It provides true A-scan measurements of eight optical ocular components in a single shot without contacting the eye [3][4][5][6][7][8][9] (Fig. 2).…”
Section: Introductionmentioning
confidence: 98%
“…When two observers measure the same parameter with the same device at different times and find similar results, the device is shown to work independently of the observer and closer to the real value of the measured parameter [17] We aimed to evaluate the intra-observer repeatability and inter-observer reproducibility of the AL-Scan, which has been tested in limited studies in the literature.…”
Section: Discussionmentioning
confidence: 99%